To protect his children [large type] - Goodnight, Linda (Love inspired., 2021)
"After a tragedy, rancher Wade Trudeau's offer of a summer housekeeping position at Sundown Ranch is the perfect cure for former teacher Kyra Mason. Only Wade left out an important part of her job - looking after his triplets! Now Kyra's falling for the three adorable toddlers, along with their love-shy cowboy dad. But when summer ends, can Kyra return to real life ... knowing she's left her heart behind?"--Back cover.